2021
DOI: 10.1186/s12884-021-03884-5
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and vulnerability of maternity services in Zimbabwe: a comparative analysis of the effect of Covid-19 and lockdown control measures on maternal and perinatal outcomes, a single-centre cross-sectional study at Mpilo Central Hospital

Abstract: Background On the 27th of March 2020 the Zimbabwean government declared the Covid-19 pandemic a ‘national disaster’. Travel restrictions and emergency regulations have had significant impacts on maternity services, including resource stock-outs, and closure of antenatal clinics during the lockdown period. Estimates of the indirect impact of Covid-19 on maternal and perinatal mortality was expected it to be considerable, but little data was yet available. This study aimed to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 16 publications
2
53
0
Order By: Relevance
“…In terms of geographical area, 19 studies were conducted in European countries [47,51,53,55,57,62,64,[67][68][69][70]75,79,83,84,88,90,92,95], 9 in North American countries [49,58,59,77,78,80,82,85,86], 9 in Sub-Saharan Africa [46,48,71,72,76,87,93,94,98], 3 in Latin America [60,91,96], 5 in the East Asia-Pacific region [50,56,61,66,81], 3 in South Asia [63,65,74], 2 in the North Africa-Middle East region [52], and, lastly, 3 studies covered various regions…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of geographical area, 19 studies were conducted in European countries [47,51,53,55,57,62,64,[67][68][69][70]75,79,83,84,88,90,92,95], 9 in North American countries [49,58,59,77,78,80,82,85,86], 9 in Sub-Saharan Africa [46,48,71,72,76,87,93,94,98], 3 in Latin America [60,91,96], 5 in the East Asia-Pacific region [50,56,61,66,81], 3 in South Asia [63,65,74], 2 in the North Africa-Middle East region [52], and, lastly, 3 studies covered various regions…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the period of analysis, 38 of the selected studies were conducted over the first months of the pandemic (February to June 2020) [46][47][48][49][50][51][52][53][54][55][57][58][59][60]62,[65][66][67][68][69][70][72][73][74][75][76][77][78][79][80]82,84,86,88,90,92,93,98]; 4 during the second stage of the pandemic (June to September 2020) [85,89,91,96]; 1 at a later stage (September to November 2020) [94]; finally, 8 analyzed the whole period (February to December 2020) [56,61,63,64,71,…”
Section: Resultsmentioning
confidence: 99%
“…3 During the lockdown, pregnant women were unable to access adequate antenatal care, failed to reach healthcare facilities on time, and faced delays in receiving care once at the hospital. [2][3][4][5][6][7][8] While emergency procedures continued to take place, all elective surg-…”
mentioning
confidence: 99%
“…The COVID-19 pandemic also impacted the utilisation of health services, as evidenced by declines in outpatient attendances. 1,7,11 A retrospective study at a tertiary hospital in Zimbabwe comparing routine maternal and perinatal statistics three months before and after the nationwide lockdown commenced found that the number of monthly hospital deliveries and caesarean section rates fell. In contrast, the number of women presenting in labour with unbooked pregnancies almost doubled.…”
mentioning
confidence: 99%
See 1 more Smart Citation